(untitled) (Historia, 2021)
Barrow’s six years at the Cape, with four long journeys, and Burchell’s close on five years ox-wagon travel gave Barrow’s Account of Travels pre-eminent authority status, with jealous attacks on rival travellers’ books and their maps. This criticism included those of Burchell, as scientist and mapmaker largely his superior. Burchell hit back with equal vituperation. Despite their enmity they advanced knowledge of the interior "least known to Europeans" (Barrow) and came together in promoting the Zuurveld as place of settlement for the 5 000 emigrants dispatched in 1820 by a government aiming to export potential radicals among the unemployed. Burchell depicted the Zuurveld as a demi-paradise to the Poor Law Commission of parliament and Barrow did the same to ministers. The anti-Xhosa ’buffer’ was never an issue and the 1834 Rharhabe invasion unforeseen. Barrow, public figure and prolific author, outshone Burchell, the retired botanist and benefactor of Kew Gardens: the latter’s fame has come late. The long-term consequence of their case for Zuurveld settlement is still undecided.